A Case Study of Tax Treaty to Generate Potential Tax Payer Revenue: A Case Study of Tax Treaty to Generate Potential Tax Payer Revenue - Erets, Yoresy; Asqolani, Asqolani (IPSAR (International Public Sector Accounting Review), 2024)
This study aims to determine the tax avoidance scheme by utilizing Tax Treaty, to find out the infirmity of the Directorate General of Taxes (DGT), the improvements that have been made, and to find out whether the Lifting Corporate Veil doctrine can be used in the Treaty Shopping case between Indonesia and other countries. Indonesia's tax ratio trend, from 2001 to 2019, tends to decline. Indonesia's economy has managed to grow but more loss on tax potential. Tax Treaty between Indonesia-Netherlands is widely used by multinational companies to conduct Treaty Shopping. This research was conducted using qualitative research methods with case studies. The object used for the case study is the Supreme Court Decision Number 135/B/PK/PJK/2017. Data were obtained from available literature and interviews. The data will be reduced and grouped according to the themes discussed. Interview data and literature study were also used for data triangulation. Based on the results of the study, it is known that the tax avoidance scheme used in the case study object is the establishment of two companies in the Netherlands then recharacterize the interest payments to dividends. Furthermore, the infirmity of the DGT in this case is that the determination of the Beneficial Owner is not based on solid evidence and the existing regulations did not regulate the Beneficial Owner criteria in detail. DGT has made many improvements, such as amending the Indonesian-Dutch Tax Treaty, adopting a multilateral instrument (MLI), issuing PER-25/PJ/2018, SE-35/PJ/2021, and has compiled General anti-avoidance rule (GAAR) in tax rule. Finally, the principle of Lifting Corporate Veil can be applied to prevent cases of Treaty Shopping, however, its application should have standardize guidelines and consider the investment side.